3-Anilinomethyl-5-chloro-1,3-benzoxazol-2(3H)-one - Aydin A.; Soyer Z.; Akkurt M.; Büyükgüngör, Orhan (International Union of Crystallography (IUCr), 2012)
In the title compound, C(14)H(11)ClN(2)O(2), the 2,3-dihydro-1,3-benzoxazole ring system is essentially planar [maximum deviation = 0.009 (2) Å] and makes a dihedral angle of 79.15 (7)° with the phenyl ring. Inter-molecular N-H⋯O and weak C-H⋯Cl hydrogen bonds occur in the crystal structure.
Keywords: Crystallography; QD901-999; Organic Papers; 3. Good health